Profiling antibody epitopes induced by mRNA-1273 vaccination and boosters - Girard, Bethany; Baum-Jones, Elisabeth; Best, Rebecca L.; Campbell, Thomas W.; Coupart, Jack; Dangerfield, Kyla; Dhal, Abhilash; Jhatro, Michael; Martinez, Brian; Reifert, Jack; Shon, John; Zhang, Minlu; et al. (Frontiers in Immunology, 2024)
Background Characterizing the antibody epitope profiles of messenger RNA (mRNA)-based vaccines against SARS-CoV-2 can aid in elucidating the mechanisms underlying the antibody-mediated immune responses elicited by these vaccines. Methods This study investigated the distinct antibody epitopes toward the SARS-CoV-2 spike (S) protein targeted after a two-dose primary series of mRNA-1273 followed by a booster dose of mRNA-1273 or a variant-updated vaccine among serum samples from clinical trial adult participants. Results Multiple S-specific epitopes were targeted after primary vaccination; while signal decreased over time, a booster dose after >6 months largely revived waning antibody signals. Epitope identity also changed after booster vaccination in some subjects, with four new S-specific epitopes detected with stronger signals after boosting than with primary vaccination. Notably, the strength of antibody responses after booster vaccination differed by the exact vaccine formulation, with variant-updated mRNA-1273.211 and mRNA-1273.617.2 booster formulations inducing significantly stronger S-specific signals than a mRNA-1273 booster. Conclusion Overall, these results identify key S-specific epitopes targeted by antibodies induced by mRNA-1273 primary and variant-updated booster vaccination.